As the christmas cookie crumbles eaudiobook - Budewitz, Leslie (Food Lovers' Village Mystery, 2018)
In Jewel Bay, all is merry and bright. At Murphy's Mercantile, AKA the Merc, manager Erin Murphy is ringing in the holiday season with food, drink, and a new friend: Merrily Thornton. A local girl gone wrong, Merrily's turned her life around. But her parents have publicly shunned her, and they nurse a bitterness that chills Erin. When Merrily goes missing and her boss discovers he's been robbed, fingers point to Merrily—until she's found dead, a string of lights around her neck. The clues and danger snowball from there. Can Erin nab the killer—and keep herself in one piece—in time for a special Christmas Eve?